Acalabrutinib Versus Investigator's Choice in Relapsed/Refractory Chronic Lymphocytic Leukemia: Final ASCEND Trial Results. Issue 12 (14th December 2022) - Ghia, Paolo; Pluta, Andrzej; Wach, Małgorzata; Lysak, Daniel; Šimkovič, Martin; Kriachok, Iryna; Illés, Árpád; de la Serna, Javier; Dolan, Sean; Campbell, Philip; Musuraca, Gerardo; Jacob, Abraham; et al.
Abstract : Acalabrutinib is a Bruton tyrosine kinase inhibitor approved for patients with chronic lymphocytic leukemia (CLL). ASCEND is the pivotal phase 3 study of acalabrutinib versus investigator's choice of idelalisib plus rituximab (IdR) or bendamustine plus rituximab (BR) in patients with relapsed/refractory (R/R) CLL. In the primary ASCEND analysis (median 16.1-month follow-up), acalabrutinib showed superior efficacy with an acceptable tolerability profile versus IdR/BR; here, we report final 4 year follow-up results. Patients with R/R CLL received oral acalabrutinib 100 mg twice daily until progression or unacceptable toxicity, or investigator's choice of IdR or BR. A total of 310 patients (acalabrutinib, n = 155; IdR, n = 119; BR, n = 36) were enrolled. At median follow-up of 46.5 months (acalabrutinib) and 45.3 months (IdR/BR), acalabrutinib significantly prolonged investigator-assessed progression-free survival (PFS) versus IdR/BR (median, not reached [NR] vs 16.8 months; P < 0.001); 42-month PFS rates were 62% (acalabrutinib) versus 19% (IdR/BR). Median overall survival (OS) was NR (both arms); 42-month OS rates were 78% (acalabrutinib) versus 65% (IdR/BR). Adverse events led to drug discontinuation in 23%, 67%, and 17% of patients in the acalabrutinib, IdR, and BR arms, respectively. Events of clinical interest (acalabrutinib vs IdR/BR) included all-grade atrial fibrillation/flutter (8% vs 3%), all-grade hypertension (8% vs 5%), all-grade major hemorrhage (3% vs 3%), grade ≥3 infections (29% vs 29%), and second primary malignancies excluding nonmelanoma skin cancer (7% vs 2%). At 4 years follow-up, acalabrutinib maintained favorable efficacy versus standard-of-care regimens and a consistent tolerability profile in patients with R/R CLL.